Philosophy of Social Sciences and Humanities and Their Relation to Linguistics - Desi Ratna Ayu; Sofyan Sauri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Language science is part of the humanities. Humanities are sciences that aim to make humans more humane. Language science will never be separated from social sciences and humanities because it will always be a part of human life for communicating, working together, and so on. The aim of this research is to describe and analyze the relationship between social sciences and humanities and linguistics. The research method used is literature review through literature studies, journal articles and books related to social sciences, humanities and linguistics, the truth of which can be accounted for. Language sciences, social sciences and humanities originate from the philosophy of science. Philosophy is a parent science that has developed very rapidly and widely. Philosophy of science becomes a mediator in the development of science, social sciences and humanities.